Analysis Of The Level Of Understanding Concepts And Critical Thinking Ability Of Students In Resolving Trigonomic Equations Using Graphs - Maulida Luka Yusrina; Siti Inganah; Octavina Rizky Utami Putri (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
This research aims to describe the level of understanding the concept and critical thinking in resolving trigonometric equations using graphs. Tests and interviews were conducted to search for data and study more in the ability to understand the concepts and critical thinking skills that students have in resolving trigonometric equations using graphs. The test given to the students is a test of the explanation with the subject of his research is a class XI student. The subject selection of six students is based on the category of ability and daily replay value of the student in trigonometric materials. The six students are each – two students of high, medium and low categories. The results showed that the ability level of understanding students ' concepts in determining the set of solving trigonomic equations using graphs, gained students understanding the concept of high and moderate levels. Students with a high level of understanding are able to fulfill all indicators – an indicator of concept comprehension. Students with the level of understanding of concepts are also meeting the indicators of understanding the concept but less appropriate, which has not been able to identify the properties of a concept. Students are also less able to classify objects based on the requirements that make up the concept. The level of students ' critical thinking ability to determine the set of solving trigonomic equations using graphs obtained by the subject of students critical thinking moderate and low levels. Students with critical thinking levels are not yet able to meet interpretation indicators, i.e. students have not been able to understand and write the answer to the problem given. Students with critical thinking levels are also underprivileged to meet critical indicators of inference. Students with critical thinking levels are less able to draw conclusions, i.e. less capable of providing the right reasons for student work. Students with critical thinking levels are low, not yet capable of meeting critical thinking indicators in determining the set solving trigonometric equations using graphs. Students have not been able to meet all indicators of critical thinking ability.